Market Orientation, Service Quality on Customer Satisfaction and Loyalty: Study on Sharia Banking in Indonesia - Ety Saraswati (Golden Ratio of Marketing and Applied Psychology of Business, 2022)
This study aims to analyze: 1) the effect of market orientation on customer satisfaction. 2) the effect of service quality on customer satisfaction. 3) the effect of market orientation on customer loyalty. 4) the influence of service quality on customer loyalty. 5) the influence of customer satisfaction on customer loyalty. 6) effect of market orientation on customer loyalty through customer satisfaction. 7) service quality towards customer loyalty through customer satisfaction. The sample of this study are 170 respondent; data collection use online-survey. The analysis technique used is Structural Equation Modeling with AMOS. the results of this study show that: 1) market orientation has a positive and significant effect on customer satisfaction. 2) service quality has a positive significant effect on customer satisfaction. 3) market orientation has an insignificant effect on customer loyalty. 4) service quality has a positive-significant effect on customer loyalty. 5) customer satisfaction has a positive-significant effect on customer loyalty. 6) market orientation has a positive and significant effect on customer loyalty through customer satisfaction. 7) service quality affects loyalty through customer satisfaction. improve market orientation so that customer loyalty is acknowledged through customer satisfaction. Further, improve market orientation through customer satisfaction to provide increased fidelity to customers.